Low-cycle fatigue performance of bimetallic steel bar considering the effect of inelastic buckling. (10th October 2022) - Wang, Fei; Hua, Jianmin; Xue, Xuanyi; Ding, Ziheng; Lyu, Yifan; Liu, Qing
Highlights: Failure performance of BSB specimens with different slenderness ratios and strain amplitudes were discussed. Effects of inelastic buckling on fatigue properties of BSB specimens were studied. A fatigue model including the effects of inelastic buckling was proposed. Abstract: Reinforcement corrosion is the main factor that affects the durability of reinforced concrete (RC) structures in corrosive environments. In this study, a bimetallic steel bar (BSB) composed of a stainless-steel cladding and a carbon steel substrate has been proposed to solve the issue of corrosion. When a RC structure is subjected to a seismic load, a reciprocating load is usually applied to the resistant member. Longitudinal steel reinforcements tend to cause fatigue failure. Inelastic buckling significantly affects the fatigue properties of the steel reinforcement. In this study, we investigated the low-cycle fatigue properties of a BSB, including inelastic buckling. Based on the experimental results, the cyclic curves of the BSB specimens exhibited a shuttle shape. The effects of the slenderness ratio ( L / D ) on the peak stress of the stable hysteretic curve of the BSB specimens were discussed. Predictive equations were suggested to quantify the effects of L / D and fatigue strain ( εa ) on the low-cycle fatigue properties of BSB specimens. The effects of L / D and εa on the variation trends of the peak stresses of BSB specimens were investigated. The failure performances of BSB specimens with different L / D and εa values were discussed. Based on the experimental results, a fatigue model was proposed to quantify the effects of inelastic buckling on BSB specimens.